The northern Pleistocene of Russia - Astakhov, Valery I. (Cambridge Scholars Publishing, 2020)
This collection of papers devoted to the Ice Age of northern Russia provides illustrated descriptions of landforms and sediments revealing former ice sheets of the arctic shelf that inundated northern Russia. It shows that a peculiar Siberian type of inland glaciation is inferred from preserved Ice Age features. This type of glacial environment implies arrested landscape evolution in continental climates with fossil glacial ice surviving within the conservative permafrost. The contributions here delve into the problem of the size and age of the last glaciation intensely discussed in the international literature.